QUANTIFICATION OF MAJOR PHYTOCHEMICALS OF SWERTIA CHIRAYITA, A MEDICINAL PLANT FROM NEPAL - Phoboo, Susanna; Silva Pinto, Marcia Da; Bhowmik, Prasanta C.; Jha, Pramod Kumar; Shetty, Kalidas (Ecoprint: An International Journal of Ecology, 2011)
Swertia chirayita is an important medicinal plant from Nepal with anti-diabetic, anti-pyretic, anti-malarial and anti-inflammatory potential and used in therapeutic herbal preparations in parts of South Asia. The main phytochemicals in crude aqueous and ethanolic extracts of different plant parts of Swertia chirayita collected from nine different districts of Nepal representing West, East and Central Nepal were quantified using HPLC/DAD (High Performance Liquid Chromatography-Diode Array Detection). The quantities of these phytochemicals were also compared between wild and cultivated plant parts of Swertia chirayita. Amarogentin, mangiferin, swertiamarin were the main phytochemicals in all extracts. The highest quantity of all the three phytochemicals was found in IL (inflorescence and leaf mixture) of all the collected plants samples. There was no significant difference in the amounts of these three phytochemicals between extracts from wild and cultivated plants. The result from this study substantiates the validity of cultivated Swertia chirayita for medicinal purposes and trade. Key words: Swertia chirayita; HPLC/DAD; Wild; Cultivated; Phytochemicals; Quantification; Mangiferin; Swertiamarin; Amarogentin DOI: 10.3126/eco.v17i0.4118 Ecoprint An International Journal of Ecology Vol. 17, 2010 Page: 59-68 Uploaded date: 3 January, 2011